Faculty experiences in publishing in Scopus-indexed journals: Challenges and strategies among higher education institutions in the Philippines - Niez, Roland A. (Edelweiss Applied Science and Technology, 2024)
Research is a cornerstone of education, with publication output often used as a key metric for research performance. This study investigates the experiences of Philippine Higher Education Institution (HEI) faculty as they work to publish in Scopus-indexed journals. By exploring faculty members' challenges, strategies, and perspectives, this research aims to inform how HEIs can enhance support for faculty in contributing to global scholarship and advancing academic careers. Using Husserl’s descriptive phenomenology, 12 faculty members from HEIs in Eastern Visayas, Philippines, were purposively selected as participants, with theoretical saturation guiding the sample size. Data was gathered through in-depth interviews and analyzed using Colaizzi's method. The study reveals four primary themes regarding the publication journey: motivation for publishing, preparation and publication process, challenges faced, and support systems. Faculty perceptions of publishing centered around five themes: career advancement and promotion, increased visibility and credibility, personal and professional satisfaction, institutional expectations, and incentives. Key challenges included financial barriers, the rigorous peer review and revision process, submission and formatting requirements, and emotional strain. To address these, participants highlighted strategies involving financial and personal investment, mentorship and collegial support, institutional resources, continuous learning, strategic journal selection, and maintaining resilience. Findings indicate that publishing in Scopus-indexed journals requires a blend of motivation, planning, and resilience, as faculty strive to contribute to knowledge and further their careers. Yet, they face substantial barriers, especially high publication fees and stringent formatting standards. Institutional support—especially through funding, mentorship, and workshops—is vital to overcoming these obstacles. For greater faculty success, institutions should cultivate a supportive research culture that recognizes and addresses the logistical and emotional demands of academic publishing.